Comparison of Growth and the Cytokines Induced by Pathogenic Yersinia enterocolitica Bio-Serotypes 3/O: 3 and 2/O: 9 - Yang, Haoshu; Gu, Wenpeng; Qiu, Haiyan; Sun, Guixiang; Liang, Junrong; Li, Kewei; Xiao, Yuchun; Duan, Ran; Jing, Huaiqi; Wang, Xin (Frontiers in Cellular and Infection Microbiology, 2017)
Pathogenic Yersinia enterocolitica is widely distributed in China where the primary bio-serotypes are 3/O: 3 and 2/O: 9. Recently, the distribution of 2/O: 9 strains are being gradually replaced by 3/O: 3 strains where presently 3/O: 3 strains are the major pathogenic Y. enterocolitica in China. To identify the growth conditions and cytokines induced by Y. enterocolitica and providing some clues for this shift, we performed competitive growth in vitro and in vivo for these two bio-serotype strains; and we also compared the cytokines induced by them in infected BALB/C mice. We found 2/O: 9 strains grew more in vitro, while 3/O: 3 strains grew more in vivo regardless of using single cultures or mixed cultures. The cytokines induced by the two strains were similar: interleukin-6 (IL-6), IL-9, IL-13, granulocyte colony-stimulating factor (G-CSF), chemokines (KC), monocyte chemotactic protein 1 (MCP-1), macrophage inflammation protein-1α (MIP-1α), tumor necrosis factor-α (TNF-α), and RANTES were statistically up-regulated upon activation of normal T cells compared to the control. The cytokine values were higher in mixed infections than in single infections except for IL-6, G-CSF and KC. The data illustrated the different growth of pathogenic Y. enterocolitica bio-serotype 3/O: 3 and 2/O: 9 in vitro and in vivo, and the cytokine changes induced by the two strains in infected BALB/C mice. The growth comparisons of two strains maybe reflect the higher pathogenic ability or resistance to host immune response for Y. enterocolitica bio-serotype 3/O: 3 and maybe it as one of the reason for bacteria shift.